RELATIONSHIP BETWEEN PLYPHARMACY AND RISK OF FALLS IN THE ELDERLY (CIPEEX, 2026)
INTRODUCTION: The increase in the elderly population in Brazil results in a higher prevalence of chronic diseases and, consequently, in the possibility of using four or more medications (polypharmacy), which is strongly associated with the occurrence of falls, doubling this risk. OBJECTIVE: This study aims to analyze the association between the use of polypharmacy and the risk of falls in elderly individuals. METHODS: This is an analytical observational cross-sectional study. A total of 84 older adults aged 60 years or older, enrolled in the Open University for the Elderly (UniAPI), were evaluated. The Timed Up and Go (TUG) test and the Downton Fall Risk Index were used to analyze the association between the number and class of medications and the risk of falls. Statistical analysis was performed using the Chi-Square Test, with a significance level of p